A magyar tanítónők, valamint a pécsi tanítóképzés a századfordulótól a második világháborúig - Takács, Zsuzsanna Mária (Közép-Európai Közlemények, 2016)
The female teacher training in Pécs was developed in 1895 in the framework of the school complex of the Notre Dame Female Canon Order invited to Pécs by Bishop János Scitovszky and it closed its doors after the World War II. Students of the institution arrived mainly from Somogy and Tolna counties, beside Baranya, thus it became the determinative female teacher school of South-Transdanubia, and this was the educational institution of the highest level for girls in this region of the country. This study focuses on the about four-decade functioning of this institution, examining mainly the social composition of students and the agglomeration area of the school in the first half of the 20th century.